Perbandingan Produktivitas Tenaga Kerja Proyek Konstruksi Saat Jam Kerja Normal Dan Lembur Di Kota Padang - Yunita, Azdharizka; Hidayat, Benny (Universitas Andalas, 2024)
Construction projects have three targets that must be achieved, namely accuracy of cost, time and quality. These three targets are influenced by work productivity. However, in the implementation of construction projects there are often delays. So, contractors usually do various ways to catch up on project delays. One of the things that contractors do to speed up work is by adding working hours outside of regular working hours or overtime. When working during regular working hours, there will be different conditions during overtime, causing differences in productivity levels between the two. The amount of productivity produced is influenced by many factors. Factors, such as field conditions and supporting facilities, job skills, age, experience, and field management. This study was conducted using observation and questionnaire methods. The observation method is carried out by measuring the implementation of work during normal and overtime hours and recording activities. Questionnaires were distributed to workers to obtain factors that affect labor productivity. The results obtained were average productivity during normal hours of 2,018 m2/hour and overtime hours of 2,043 m2/hour. The average LUR value during normal working hours is 61.39% and overtime hours is 64.66%. In addition, factors that greatly influence are workers' wages, weather conditions, work area conditions, and lack of rest time.